Enacting care by being experts and managing relationships: A discourse analysis of chief medical officer of health media briefings during the COVID-19 pandemic - Sudit Ranade; Judith Belle Brown; Tom Freeman; Amardeep Thind (Elsevier, 2023)
In Canada, Chief Medical Officers of Health (CMOHs) are responsible for protecting and promoting the health of their respective populations, but few studies have examined this role and its connections with the practice of medicine. In Canada and elsewhere, CMOHs and other public health physicians have articulated their actions as caring for their populations as patients. In order to understand the components of enacted care, this study is a functional discourse analysis of transcribed CMOH media briefings at three time points in five Canadian jurisdictions during the first full year of the COVID-19 pandemic (2020). Transcripts were coded and analysed in an iterative, comparative process to understand the content, actions and purpose of CMOH communication during media briefings. CMOHs used their public communications to enact their care of populations by "being experts" and "managing relationships". "Being experts" involved describing disease characteristics, assessing risk and evidence, framing risk and evidence, and making judgments about intervention and exemption. "Managing relationships" involved self-regulating emotions, acknowledging the emotions of others, seeking adherence and collaboration, and setting expectations and boundaries. The findings suggest that traditional biomedical roles were performed by CMOHs in media briefings, implying the existence of a patient (or multiple patient-like relationships) and supporting further research into the processes by which public health physicians care for populations as patients.